Words and images an essay on the origin of ideas - Gauker, Christopher (Oxford : Oxford University Press, 2011)
For centuries philosophers have attempted to derive concepts from perceptual representations but have failed to explain how the mind generates the building blocks of thought. Gauker addresses this problem in a new account of imagistic cognition. He shows that much of cognition occurs by means of mental imagery, without the help of concepts.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Idea (Philosophy); Comprehension (Theory of knowledge)